What is known about personal reputation? A systematic literature review - M. Victoria Carrillo-Durán; Ramsés Cabrera-Gala; Laura B. Sánchez-Baltasar (Heliyon, 2023)
This systematic literature review encompassed the results of previous research on personal reputation and found opportunities in state of the literature to guide future research in communication, management, and other disciplines in the social sciences. A content analysis was conducted of 91 manuscripts from 1984 to November 2022, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The findings suggest that the amount of literature on personal reputation has increased since 2006; however, it is still in a developing stage. Due to its scarcity, it is advisable to conduct more qualitative and probability studies. For this review, several of the most cited articles are probably pioneering manuscripts that contributed to building the personal reputation construct. This review establishes a total of six categories for guiding future research opportunities on personal reputation. To facilitate the classification of the different future research opportunities, some types of areas suggested by Gomez-Trujillo et al. were considered. The discussion of future research opportunities includes categories like Causes and Effects, Inventories and Scales, Online and Digital Context, Organizational and Group Environments, Leaders and Top Management Executives, and Theory-building. On the other hand, this study could be considered the first step towards future research on how personal reputation influences audiences' opinions and perceptions in different research fields. It also opens the possibility of conducting more specific systematic literature reviews on this topic. Finally, this manuscript offers an overview of the present and the future of construct of personal reputation in the social sciences.